Acoustic manipulation of fractal metamaterials with negative properties and near-zero densities. (23rd December 2021) - Wu, Guanghua; Ke, Yibo; Zhang, Lin; Tao, Meng
Abstract: Acoustic metamaterials have high potential in diverse applications, including acoustic cloaking, sound tunneling, wavefront reshaping, and sound insulation. In the present study, new metamaterials consisting of spatially coiled units are designed and fabricated to manipulate sound waves in the range of 0–1600 Hz. The effective acoustic properties and band diagrams of the metamaterials are studied. The simulation and experimental results demonstrate that the metamaterials provide an effective and feasible approach for designing acoustic devices such as sound cloaking and insulators.